1998
DOI: 10.1001/archopht.116.8.1053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pupillary Dilation on Corneal Optical Aberrations After Photorefractive Keratectomy

Abstract: Background: Complaints of glare, halos, and disturbances of night vision after photorefractive keratectomy (PRK) probably result from changes in the corneal aberration structure induced by the laser ablation procedure. The purpose of this article is to characterize changes in the corneal aberration structure after PRK and to demonstrate the effect of pupil dilation on these changes. Methods: Videokeratographs obtained preoperatively (n = 112) and at 1 (n = 94), 3 (n = 103), 6 (n = 91), 12 (n = 60), 18 (n = 53)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
99
1
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(113 citation statements)
references
References 48 publications
10
99
1
3
Order By: Relevance
“…21,[29][30][31] We also found that surgically induced spherical aberrations, coma aberrations and total higher-order aberrations all increased in higher myopic correction. It is understandable that laser-induced aberrations increase with depth of laser ablation.…”
Section: Discussionsupporting
confidence: 54%
“…21,[29][30][31] We also found that surgically induced spherical aberrations, coma aberrations and total higher-order aberrations all increased in higher myopic correction. It is understandable that laser-induced aberrations increase with depth of laser ablation.…”
Section: Discussionsupporting
confidence: 54%
“…The RMS of third-and fourth-order Zernike components (Z 3 -3 to Z 3 3 , Z 4 -4 to Z 4 4 , respectively) were used to represent coma-and spherical-like aberrations, respectively. [20][21][22][23][24] …”
Section: Measurement Of Hoasmentioning
confidence: 99%
“…[15][16][17][18][19] Letter-contrast sensitivity was measured with CSV-1000LV chart (Vector Vision, Columbus, OH, USA). This instrument uses letter optotypes all of which were the same size and of low spatial frequency (2.4 cycle/1).…”
mentioning
confidence: 99%